2008
DOI: 10.1681/asn.2007121368
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Mediates Recruitment of RNA Polymerase II to Target Genes in Acute Renal Failure

Abstract: Acute renal failure (ARF) sensitizes the kidney to endotoxin (LPS)-driven production of cytokines and chemokines. This study assessed whether this LPS hyperresponsiveness exists at the genomic level. Three heterogeneous mouse models of ARF were studied: Maleate nephrotoxicity, unilateral ureteral obstruction, and LPS preconditioning. In all cases, LPS was injected approximately 18 h after injury was induced, and over the next 0 to 90 min, RNA polymerase II recruitment to the genome at three LPS-responsive gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 41 publications
5
63
1
1
Order By: Relevance
“…Thus it is difficult to ascertain which of these two processes initiated and maintained the in vivo mRNA elevations, as discussed above. Assessments of Pol II binding to target genes can help resolve this issue, given that Pol II is the enzyme that drives transcription and its binding to gene loci serves as a semiquantitative index of transcription rates (16,21,24,26). Given these considerations, we assessed Pol II binding to each of the four target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is difficult to ascertain which of these two processes initiated and maintained the in vivo mRNA elevations, as discussed above. Assessments of Pol II binding to target genes can help resolve this issue, given that Pol II is the enzyme that drives transcription and its binding to gene loci serves as a semiquantitative index of transcription rates (16,21,24,26). Given these considerations, we assessed Pol II binding to each of the four target genes.…”
Section: Discussionmentioning
confidence: 99%
“…These authors demonstrated in vivo increased RNApolymerase II density at TNF-α, monocyte chemotactic protein-1 (MCP-1) and heme oxygenase-1 (HO-1) loci after LPS injection in mice. This effect was related to selective histone methylation and was enhanced by different nephrotoxic stimuli [20]. These AKI-associated epigenetic alterations of tubular cells may be responsible for the above-mentioned increase in circulating inflammatory mediators.…”
Section: Tubular Cellsmentioning
confidence: 95%
“…Mice were injected with either LPS or cisplatin, as noted above. Either 24 h (LPS-injected mice; n ϭ 5) or 48 h later (cisplatin-injected mice; n ϭ 4), proximal tubules were isolated as previously described (16). The tubules were then extracted for both RNA and total protein and assayed for both Hpx mRNA and Hpx protein levels, as noted above.…”
Section: Assessments Of Hpx Protein and Mrna Levels In Isolated Proximentioning
confidence: 99%
“…The above LPS experiment was repeated, but following tubule isolation, the tubules were incubated in the presence or absence of actinomycin D (2 g/ml) to block de novo RNA synthesis, as previously described (16). By so doing, changes in Hpx mRNA levels reflect Hpx degradation rates.…”
Section: Assessment Of Hpx Mrna Stabilitymentioning
confidence: 99%